Terminal Deoxynucleotidyl Transferase and T7 Exonuclease-Aided Amplification Strategy for Ultrasensitive Detection of Uracil-DNA Glycosylase - Du, Yi-Chen; Cui, Yun-Xi; Li, Xiao-Yu; Sun, Guo-Ying; Zhang, Yu-Peng; Tang, An-Na; Kim, Kwangil; Kong, De-Ming (Analytical chemistry (Washington), 2018)
As one of the key initiators of the base excision repair process, uracil-DNA glycosylase (UDG) plays an important role in maintaining genomic integrity. It has been found that aberrant expression of UDG is associated with a variety of diseases. Thus, accurate and sensitive detection of UDG activity is of critical significance for biomedical research and early clinical diagnosis. Here, we developed a novel fluorescent sensing platform for UDG activity detection based on a terminal deoxynucleotidyl transferase (TdT) and T7 exonuclease (T7 Exo)-aided recycling amplification strategy. In this strategy, only two DNA oligonucleotides (DNA substrate containing one uracil base and Poly dT probe labeled with a fluorophore/quencher pair) are used. UDG catalyzes the removal of uracil base from the enclosed dumbbell-shape DNA substrate to give an apyrimidinic site, at which the substrate oligonucleotide is cleaved by endonuclease IV. The released 3′-end can be elongated by TdT to form a long deoxyadenine-rich (Poly dA) tail, which may be used as a recyclable template to initiate T7 Exo-mediated hybridization–digestion cycles of the Poly dT probe, giving a significantly enhanced fluorescence output. The proposed UDG-sensing strategy showed excellent selectivity and high sensitivity with a detection limit of 1.5 × 10–4 U/mL. The sensing platform was also demonstrated to work well for UDG inhibitor screening and inhibitory activity evaluation, thus holding great potential in UDG-related disease diagnosis and drug discovery. The proposed strategy can be easily used for the detection of other DNA repair-related enzymes by simply changing the recognition site in DNA substrate and might also be extended to the analysis of some DNA/RNA-processing enzymes, including restriction endonuclease, DNA methyltransferase, polynucleotide kinase, and so on.